Effect of mental training on the performance of college age distance runners - Spino, M. P.; Straub, W. F. (The Sport Journal, 2014)
The purpose was to determine if Event Rehearsal Imagery (ERI) and Internal guided Imagery with Distractions (IGID) resulted in improvements in the running performance of college students. The participants (N = 74) were students at Kenyatta University in Nairobi, Kenya. Cooper`s 12 min run test was used to assess running performance. Following 8-weeks of training, findings indicated that there was a statistically significant difference (0.05 level) in running performance between the Event Rehearsal Imagery (n = 29), Event Rehearsal Imagery with Distractions (n = 16) and the Control group (n = 29). Overall, there was a significant mean difference in running among male (n = 47) and female (n = 27 participants).